VOLCANIC ROCK GEOCHEMISTRY AND TECTONIC IMPLICATION OF THE LUOBADUI FORMATION ON THE GANGDESE ZONE, XIZANG (TIBET) - Geng Q.R.; Wang L.Q.; Pan G.T.; Zhu D.C.; Liao Z.L.; Li G.M.; Li F.Q.; Jin Z.M. (My University, 2007)
The Mesozoic and Cenozoic volcanic rocks in the Gangdese zone is an important field of Tibetan geologic studies. The Late-Paleozoic volcanic rocks and their tectonic settings however, Still remain unstudied. The Permian stratigraphy represented a slow regression process with two volcanic events, characterizing an active margin. We measured key geologic sections at Tangjia and Leqingla of the Luobadui Fm. and analyzed volcanic rock samples for major and trace elements and Sr, Nd and Pb isotopes. These suggest that Permian was a period of arc formation in the Gangdese zone. From lower (possible early Permian) to upper part (middle Permian) of the Luobadui basalts, the MgO contents drop from 7.43% to 3.99% and Al2O3 contents increase from 15.54% to 17.57%. The later resembles high-Al basalts of island arc. Meanwhile, the ∑REE values increase from 54.12 × 10-6 to 108.82 × 10-6 and LREE/HREE ratioes from 3.00 to 5.40. The basaltic rocks of the Luobadui Fm. show significant Nb and Ta negative anormallies. Geochemical studies suggest that basalts in the Luobadui Fm. represent a Permian initial arc. Early Permian basalts derived from a mixed source of slightly-depleted mantle and lower crustal materials at thin crust. Up to middle Permian, more crust components were involved in source regions or primitive magma at thicker crust, and suggest evolution to a continental arc. The Gangdese Permian arc was resulted from the southern subduction of the paleo-Tethys.
Keywords: GANGDESE ZONE IN TIBET; ISLAND ARC; PERMIAN; STRATIGRAPHY; VOLCANIC ROCK GEOCHEMISTRY; Paleozoic::Permian; Палеозой::Пермская